Springback mechanism analysis and experimentation of orthodontic archwire bending considering slip warping phenomenon. (7th May 2018) - Jin-gang, Jiang; Xue-Feng, Ma; Yong-De, Zhang; Yi, Liu; Biao, Huo
Malocclusion is a common oral disease. Fixed appliance technology is the most common and effective malocclusion orthodontic treatment method, and the key step of fixed appliance technology is the bending of orthodontic archwire. Because the slip warping phenomenon exists in the process of orthodontic archwire bending, it is difficult to realize rapid and accurate bending of the customized orthodontic archwires. A bending springback mechanism model considering the slip warping of the archwire in the process of bending is established. The influence of the slip warping phenomenon of the archwire between the fixed mold and the rotation mold is considered in the analysis of the springback mechanism. The bending process of archwire is divided into two stages: elastic deformation and plastic deformation, based on the variety of the bending radius in the bending process. A springback mechanism model of the orthodontic archwire is established. The springback mechanism model of the orthodontic archwire is analyzed and compensated based on the characteristics of the robot structure. An archwire bending experiment is carried out to verify the correctness of the springback mechanism model of the orthodontic archwire.